FAKTOR-FAKTOR PENYEBAB PERUBAHAN TRADISI SILAT DALAM ADAT PERNIKAHAN PADA MASYARAKAT MUARA LEMBU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Tia Nopriantari; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Abstract: Abstract: This research is motivated by the factors that cause changes in the tradition of silat in marriage customs in the muara lembucommunity of the singingi sub-district of Kuantan singingi district, where this silat is usually carried out in a traditional wedding but today the tradition is very rarely carried out by the estuary of the ox. The formulation of the problem in this study is